The effect of adjunctive LASER application on periodontal ligament stem cells - Ponnaiyan, Deepa; Rughwani, Roshan R.; Shetty, Ganesh; Mahendra, Jaideep (Frontiers in Cell and Developmental Biology, 2024)
Periodontitis is a disease primarily characterized by inflammation and an interplay of bacteria and endotoxins which impacts the soft and hard tissues of the periodontium. The disease leads to significant cellular damage and tissue loss which eventually culminates in bone loss (Hajishengallis, 2022;Zenobia and Darveau, 2022;Vitkov et al., 2023). The extent of hard and soft tissue loss determines the treatment strategies; however, mechanical debridement remains the cornerstone of periodontal treatment which turns the inflammatory state of the periodontium to a resolving state (Albeshri and Greenstein, 2022; Laleman et al., 2022). Periodontal treatment not only involves elimination of inflammatory and bacterial component from the diseased tooth supporting tissues, but also comprises of regeneration of deteriorated periodontal structures in amenable cases which serves as the bedrock to principles of tissue engineering that engages application of appropriate cells, growth factors and scaffolds(